Abraham Maslow: The Needs Hierachy - Yahaya, Azizi (2008)
Abraham Maslow is considered to be the father of Humanistic Psychology. Maslow developed a theory of personality that has influenced a number of different fields, including education. This article is about the hierarchy needs of human in development of motivation. There are 7 web sites that have been analyse. This article divided to 3 part. The first part is explaining ‘Introduction’ of Maslow hierarchy of needs. The second part is explaining ‘A Theory Of Human Motivation’ including ‘Further Characteristics Of The Basic Needs’. The third part is about ‘Maslow Hierarchy Of Needs’. The last part is explaining ‘The Importance Of Maslow Theory For Education’ including ‘Teachers’ Role’ and ‘Importance For Students’.